Keteladanan Kepemimpinan Paulus terhadap Kepemimpinan Guru Kristen Berdasarkan Kisah Para Rasul 20:17-38 - Genti Turnip; Jamli Barus; Liantri Fena Silitonga (Sekolah Tinggi Teologi Baptis Medan, 2022)
This study aims to determine how much influence the understanding of Paul's exemplary leadership has on the leadership of Christian teachers at SMK Negeri 2 Medan, with the research hypothesis: